Anti-Tubercular Activity of Fruits of Prunus Armeniaca (L.) - Jaya Sehgal; Dr.P.Siddheswaran; Dr.K.L.Senthil Kumar; Mrs. T. Karthiyayini. (International Journal of Pharma and Bio Sciences, 2010)
The antitubercular effect of aqueous and ethanol extracts prepared from fruits of Prunus armeniaca (L.) was evaluated on Mycobacterium tuberculosis using cup plate method. The zone of inhibition was taken to assess antitubercular activity. The results showed that ethanolic extract have more significant antitubercular activity as compared to aqueous extract.